The Role of Medical Personnel Responsiveness and Competency in Improving Brand Image and The Annual Number of Hospital Visits - Renny Hartanti; Hasyim Hasyim; Duta Liana (Eduvest - Journal of Universal Studies, 2025)
In 2023, there has been a decrease in the number of general patients visiting hospitals, which is a serious concern for the management. The factor suspected to affect this decline is the public's perception of the responsiveness and competence of the services provided by the hospital. The purpose of this study is to empirically reveal the influence of responsiveness and competence on patients' decisions to visit hospitals with brand image as an intervening variable. The type of research is included in the quantitative with a cross-sectional study design. The results of the analysis prove that responsiveness and competence affect the patient's decision to visit the hospital, with brand image as an intervening variable. The implication of these findings is the need to improve the variables that affect the brand image, such as staff knowledge, service skills, and managerial considerations in providing responsive and competent services. These improvement efforts can improve the hospital's brand image and ultimately help attract more patients to re-choose the hospital as their healthcare provider.